Disfluency Meets Cognitive Load in Multimedia Learning: Does Harder‐to‐Read Mean Better‐to‐Understand?. Issue 4 (7th February 2014) - Eitel, Alexander; Kühl, Tim; Scheiter, Katharina; Gerjets, Peter
Summary In a series of four experiments, we examined the impact of disfluency in multimedia learning by testing contrasting predictions derived from disfluency theory and cognitive load theory against each other. Would a less legible text be beneficial to learning when accompanied by pictures, and what would be the role of less legible pictures? Students (N = 308) learned with text and pictures that were either easy‐to‐read (i.e., fluent) or harder‐to‐read (i.e., disfluent) about how a toilet flush works (Experiments 1–3) and about how lightning develops (Experiment 4). In line with disfluency theory, a disfluent text led to better performance in the transfer test and to more invested mental effort in Experiment 1. However, these beneficial effects could not be replicated in Experiments 2, 3, and 4, leaving open questions regarding the stability and generalizability of the disfluency effect, and thus raising concerns regarding its impact for educational practice. Copyright © 2014 John Wiley & Sons, Ltd.